Perlindungan Hukum terhadap Peralihan Hak Atas Kapal Bobot diatas 7 Gross Tonnage melalui Jual Beli Bawah Tangan - Syahputra, Yudha; Yuhelson, Yuhelson; Halim, Anriz Nazaruddin (Universitas Islam Negeri Alauddin Makassar, 2024)
In the reality that occurs in society which has become a customary law where it starts from the element of mutual trust and then agrees on the price and object, then the parties continue the sale and purchase agreement by buying and selling under the hand with receipts. So there was a levering of the transfer of ownership of the ship to the buyer. Related to Article 5 letter a of the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 39 of 2017 concerning Registration and Nationality of Ships requires ships that are registered for ownership in Indonesia, namely ships with size 7 (Gross Tonnage). The method used in this study is normative juridical research, namely normative juridical research is an approach using a set of laws and regulations and other legal materials. The research approach used is to review laws and regulations as the main point of analysis in reviewing and discussing legal issues. From the results of the research, it is obtained that in order to avoid a dichotomy between government regulations that regulate a transfer of rights and notary deeds and the reality in the field, it is necessary that imperative provisions regarding the transfer of rights to ships with a weight of more than 7 gross tonnage are clearly regulated in the provisions that are included in the hierarchy of laws and regulations as per Law of the Republic of Indonesia Number 12 Year 2011 concerning the Formation of Laws and Regulations.